HUBUNGAN SANITASI FISIK RUMAH DENGAN KEJADIAN ISPA PADA BALITA DI TPA TAMANGAPPA ANTANG MAKASSAR TAHUN 2020 - Andi Suci Indah Lestari; Rosdianah Rahim; Andi Irhamnia Sakinah (Program Studi Akuntansi IKOPIN, 2022)
ARI or Acute Respiratory Infection is an acute infection that affects one or more respiratory tract organs caused by pathogens such as bacteria, viruses, or fungi. cases amounted to 147,848 people. This study aims to determine the relationship of the physical environment in the form of ventilation, house humidity, residential density, house lighting, exposure to cigarette smoke, and use of mosquito repellent with the incidence of ARI in toddlers. This research is a quantitative research with a cross sectional study design which was conducted at the TPA Tamangappa Antang Makassar with a sample of 90 children under five using the non-random sampling technique, the type of purposive sampling. Data collection from respondents was done using questionnaires and observation sheets. Data analysis used chi square test p <0.05 and phi test 0.001 < < 1.00. The results showed that there was a relationship with ventilation (p = 0.000, = 0.433), there was a relationship with humidity (p = 0.000, = 0.456), there was a relationship with occupancy density (p = 0.036, = 0.264), there was a relationship with lighting house (p=0.002, =0.344), there was a relationship with exposure to cigarette smoke (p=0.000, =0.531), and there was a relationship with the use of insect repellent (p=0.001, =0.382).